2015
DOI: 10.1590/1678-4499.142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum on the elongation and external morphology of root tips in two maize genotypes

Abstract: AbstrAct:The objective of this study was to evaluate the effects of toxic levels of aluminum (Al) on the growth and external morphology of root tips in two maize genotypes with differential Al tolerance. The maize genotypes UFVM-100 (Al-sensitive) and were treated with 0 and 50 µM Al in a 0.5 mM CaCl 2 solution at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
(45 reference statements)
1
11
0
4
Order By: Relevance
“…2f). Therefore, BRS1010 was proven to show higher sensitivity to Al as previously reported for other sensitive maize genotypes (Souza et al 2016). Although Al induced damage to the root system, the short time of Al exposure (5 days) was apparently not enough to trigger nutritional disturbances in roots, except in the content of Mg (both genotypes) and Ca (BRS1055), which reduced (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…2f). Therefore, BRS1010 was proven to show higher sensitivity to Al as previously reported for other sensitive maize genotypes (Souza et al 2016). Although Al induced damage to the root system, the short time of Al exposure (5 days) was apparently not enough to trigger nutritional disturbances in roots, except in the content of Mg (both genotypes) and Ca (BRS1055), which reduced (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…The primary site of aluminum accumulation and damage is still a matter of debate. In many species, the root apex was identified as the primary site of perception of aluminum toxicity, and consequently the expression of tolerance ( Kollmeier et al, 2000 ; Yang et al, 2008 ; Horst et al, 2010 ; Motoda et al, 2011 ; Souza et al, 2016 ). Sivaguru et al (2013) demonstrated that Al affects approximately the 1–3 mm portion of the roots in sorghum lines sensitive to the metal.…”
Section: Discussionmentioning
confidence: 99%
“…The Al accumulation changed the organization and structure of the root border cells (Fig. 3) as observed in cowpea (Kopittke et al 2008), maize (Souza et al 2015) and soybean (Kopittke et al 2015;dos Reis et al 2018) after exposure to Al. In addition to the damages to the root system, Al can affect the absorption of water and nutrients by plants (Kochian 1995).…”
Section: Discussionmentioning
confidence: 80%